Human Rights and Sports Mega-Events: The Role of Moral Disengagement in Spectators. (February 2018) - Schofield, Edward; Rhind, Daniel J. A.; Blair, Richard
Human rights issues such as freedom of speech, equality, and displacement are repeatedly connected with the hosting of sports mega-events. Governments and event organizers require public backing to ensure these events remain sustainable; this study provides an explanation as to how the general populations continue to provide this support in spite of these concerns through the framework of Bandura's social cognitive theory of moral agency. Four focus groups consisting of 18 individuals who had attended a sports mega-event were carried out using a semistructured format, covering the topics of freedom, protection, access, equality, and ability. Subsequently, the data were analyzed deductively using definitions of the mechanisms of moral disengagement. The findings provide preliminary evidence of moral disengagement in members of the public who support sports mega-events. Implications for human rights organizations and other key stakeholders are discussed.